STUDY ON THE EFFECTS OF SOIL-CEMENT STABILIZATION IN THE LOWER ROAD FOUNDATION LAYER USING SPENT BLEACHING EARTH STABILIZER IN TERMS OF SOIL PHYSICAL PROPERTIES - Hafiz, Idham; Bachtiar, Vivi; Rustamaji, R. M. (Fakultas Teknik Universitas Tanjungpura, 2023)
In road construction planning, soil plays a primary role that will be examined. In geotechnical engineering, soil stabilization is one of the engineering sciences and efforts to enhance soil characteristics. Unbeknownst to many, ideas and concepts are generated to create new innovative materials that can replace or supplement existing materials. Based on this, the concept of utilizing spent bleaching earth (SBE) waste material emerged. With the advancement of engineering knowledge, particularly in the field of geotechnical engineering, soil stabilization is employed as an effort to improve soil characteristics. By utilizing SBE and cement as materials for soil stabilization in dams, the changes in the physical properties of the embankment soil before and after stabilization are examined. The physical property results are obtained through testing. Each obtained result is compared against the lower road foundation layer specifications based on the General Specifications for Road and Bridge Construction Works 2018 (Revision 2). Based on the testing and analysis, the plasticity index value with an optimum content of 10% and a curing time of 14 days, which is 7.576%, has met the requirements for constructing Class B roads' lower road foundation layer.